Sudden death in case of anorexia nervosa: consideration of the mechanism of death - Bogdanović, Milenko; Popović, Vesna; Atanasijević, Tatjana; Radnić, Bojana; Petrović, Tijana; Milošević, Veljko (Medical Research, 2024)
ABSTRACT Introduction: Anorexia nervosa is a severe chronic psychiatric disorder with often underestimated prevalence. Anorexia nervosa patients can die due to natural causes, such as severe heart problems, organ failure, malnutrition, or unnatural causes, such as suicide. However, mechanism of death in anorexia nervosa is poorly understood. Patient review: Our paper describes a case of sudden death of a 22-year-old woman suffering from anorexia nervosa. The autopsy showed severe malnutrition. Upon opening of the abdominal cavity, extremely dilated stomach (without signs of wall necrosis or rupture) was noted. Biochemical findings showed that the vitreous chloride, sodium and potassium levels were markedly low, suggesting antemortem significant hypokalemia. There were no biochemical signs of severe hypoglycemia and dehydration. As cardiac disease is a significant cause of death in AN, aggravation caused by concurrent biochemical derangement must be taken into account. The precise role of gastric dilatation in the occurrence of death is possible, but remain questionable. Conclusion: The possible mechanism of death in this case could have been disruption of the heart rhythm in an arrhythmogenic state due to the imbalance of electrolyte levels or by gastric dilatation related vagal activation.